The Current Status of Research on Gibberellin Biosynthesis - Hedden, Peter (Plant & cell physiology, 2020)
Gibberellins are produced by all vascular plants and several fungal and bacterial species that associate with plants as pathogens or symbionts. In the 60 years since the first experiments on the biosynthesis of gibberellic acid in the fungus Fusarium fujikuroi, research on gibberellin biosynthesis has advanced to provide detailed information on the pathways, biosynthetic enzymes and their genes in all three kingdoms, in which the production of the hormones evolved independently. Gibberellins function as hormones in plants, affecting growth and differentiation in organs in which their concentration is very tightly regulated. Current research in plants is focused particularly on the regulation of gibberellin biosynthesis and inactivation by developmental and environmental cues, and there is now considerable information on the molecular mechanisms involved in these processes. There have also been recent advances in understanding gibberellin transport and distribution and their relevance to plant development. This review describes our current understanding of gibberellin metabolism and its regulation, highlighting the more recent advances in this field.
Keywords: Gibberellins; Gibberellin metabolism; Plant Growth Regulators; Metabolic Networks and Pathways; rostliny; gibereliny; regulátory růstu rostlin; metabolické sítě a dráhy; Plants